T3ST code: turbulent transport in tokamaks via stochastic trajectories - D.I. Palade; L.M. Pomârjanschi (Nuclear Fusion, 2025)
We introduce the Turbulent Transport in Tokamaks via Stochastic Trajectories (T3ST) code, designed to address the problem of turbulent transport using a statistical approach complementary to gyrokinetics. The code employs test-particle methods to track the dynamics of charged particles in axisymmetric magnetic equilibria, accounting for both turbulence and Coulomb collisions. The turbulence is decoupled from plasma dynamics and represented through a statistical ensemble of synthetic random fields with specified spectral properties. This approach enables T3ST to compute transport coefficients as Lagrangian correlations—orders of magnitude faster than gyrokinetic codes.